Eficácia, uso de medicamentos e gastos no tratamento da artrite reumatoide no sistema único de saúde, 2003 a 2006 - Juliana de Oliveira Costa (2012)
Rheumatoid arthritis (RA) is a chronic autoimmune incapacitating disease, which leads to loss of quality of life and causes economic impacts for patients and for society. Pharmacological treatment includes the use of biological agents, such as infliximab (IFX), which are indicated for patients who have failed treatment with therapeutic disease-modifying anti-rheumatic drugs (DMARD). In the Brazilian Unified Health System (Sistema Único de Saúde - SUS) these medicines are available through the Specialized Pharmaceutical Service (Componente Especializado da Assistência Farmacêutica- CEAF). Considering the increasing drug spending and the national shortage of studies on the subject, it is timely to conduct studies that assess the efficacy of the drugs, the profile of users and the expenses related to therapy in SUS. To evaluate the efficacy and safety of IFX containing regimens in combination with methotrexate (MTX) versus MTX alone or combined with other DMARD we conducted a systematic literature review and meta-analysis. We assessed clinical efficacy outcomes, radiographic progression, withdrawals and adverse events. The results of clinical efficacy, radiographic progression and withdrawals due to lack of efficacy favored the IFX + MTX scheme especially during initial treatment. There was no statistical significant difference in adverse events. It was found that high doses IFX was as effective as the standard dose of IFX. The profile of users and related expenses of DMARD and IFX therapy in users of SUS between 2003 and 2006 were assessed by a construction of a cohort from the deterministic / probabilistic relationship of the Outpatient Information System databases (Sistema de Informação Ambulatorial do SUS). Analyzes were stratified by clinical and socio-demographic characteristics and follow up period. We calculated the average monthly expenses for each individual follow-up year and the factors that influenced it. The cohort consisted of 26,228 patients, mostly female, between 40 and 59 years, residing in Southeast and with entry year into the CEF in 2006. The most frequents diagnosis were Felty's syndrome and unspecified seropositive RA. The drug spending accounted for 92.17% of the costs of outpatient procedures. Medicines for RA totalized R$74,306,087.18, of which infliximab accounted for 70% of the value. The median monthly spending per capita was R$3,466.03 for patients using infliximab compared to R$ 143.85 for patients treated with DMARD. Considering the results of the two studies, we concluded that drugs were the main expense recorded in the system for health care to outpatient treatment of RA patients from 2003 to 2006, with high economic impact due to infliximab. However, the use of this medicine combined with MTX was more effective than treatment with MTX alone or in combination for patients previously treated or not, and presented good tolerability. Its use compared to conventional DMARD should consider the ability to reduce functional loss balanced by their high cost and small clinical difference during longer follow-up periods. Furthermore, in cases of poor response to standard dose of IFX switching to another biologic agent may be a suitable strategy.